Parenthood and couples' relative earnings in Norway 2005-2014 - Janna Bergsvik; Kenneth Aarskaug Wiik; Ragni Hege Kitterød (Statistics Norway, Research Department, 2018)
In the current paper, we investigate within-couple inequality in earnings using Norwegian register data on married and cohabiting couples. We are particularly interested in assessing whether the negative relation between children and women's relative earnings changed during the study period 2005 to 2014. In this period, work-family policy measures meant to facilitate mothers' employment and promoting fathers' family involvement were strengthened, and there was a sharp increase in women's level of education. Controlling for demographic and socioeconomic variables, results showed that women on average still earn less than their male partners and that the presence of small children in the household was negatively related to women's earnings. However, results from interaction models showed that the negative association between having young children and women's relative earnings was reduced during the study period. Additional analyses confirmed that this latter finding was mainly due to an income reduction among new fathers.
Keywords: D13; J12; J13; J16; 330; Women's relative earnings; Parenthood; Cohabitation; Marriage; Family policy; Gender equality